La pedagogia di Leopardi e la matrice recanatese. Annotazioni - Michele Zedda (Firenze University Press, 2017)
Leopardi's pedagogical ideas are influenced by cultural milieu of Recanati. Leopardi opposes this little, narrow reality, but there he also observes humanity (children in particular), with theorectical outcome. The context of Recanati is fundamental in examining Leopardi's pedagogy.